Safety of mRNA BNT162b2 COVID-19 (Pfizer-BioNtech) vaccine in children aged 5-11 years: Author's reply to correspondence - Giancarlo Ripabelli; Angelo Salzo; Manuela Tamburro (Taylor & Francis Group, 2023)
Dear Editor, We would like to reply to "Safety of mRNA BNT162b2 COVID-19 (Pfizer-BioNtech) vaccine in children aged 5-11years: Correspondence" regarding our article entitled "Safety of mRNA BNT162b2 COVID-19 (Pfizer-BioNTech) vaccine in children aged 5-11years: Results from an active pharmacovigilance study in central Italy."